Zeros of higher derivatives of meromorphic functions in the complex plane. Issue 4 (12th October 2012) - Yamanoi, Katsutoshi
Abstract : We prove the Gol'dberg conjecture, which states that the frequency of distinct poles of a meromorphic function f in the complex plane is governed by the frequency of zeros of the second derivative f ″. As a consequence, we prove Mues' conjecture concerning the defect relation for the derivatives of meromorphic functions in the complex plane.